أهمية تقدير الأسترات الألكيلية للأحماض الدهنية وإمكانية استخدامها كمؤشر لتصنيف زيت الزيتون - العاصي محمود (Latakia University Journal -Biological Sciences Series, 2019)
طورت في هذا البحث طريقة جديدة لتقدير الأسترات الألكيلية حيث عُزلت باستخدام عمود فصل حشوته من السيليكاجل 1غ (SPE) ثم قدرت بجهاز الكروماتوغارفيا الغازية G.C)). قسمت عينات الدراسة إلى 3 مجموعات: زيوت زيتون بكر ممتازة، زيوت ذات عيوب حسية شائعة، وزيوت زيتون مُحللة بواسطة فريق تذوق. حيث إنه في المجموعة الأولى تم تقدير الأسترات في 49 عينة، وأشارت النتائج بأنه في الـ 96% من العينات كانت الكمية الكلية من الأسترات الألكيلية أقل من 75 ملغ\كغ، وبالنسبة للزيوت التي تعلو هذه القيمة فإن العلاقة بين الأسترات (إيتيلية\ميتيلة) كانت أقل من 1,5، ولكن الزيوت التي لاتنطبق عليها الشروط السابقة فإنها تفقد صفة الجودة. أما في المجموعة الثانية فقدّرت الأسترات في 5 عينات زيوت زيتون ذات عيوب حسية شائعة (الهري، والتخمر، والعكر، والعفن، وتزنخ وزيتون مصاب بالصقيع)، وقد وجد أن التغيرات الناتجة عن عمليات أنزيمية أو تخمرية ترافقت بتراكيز مرتفعة من الأسترات الميتيلية (62-777) والإيتيلية (430-1853) والعلاقة بينها (7,3-2,0). بينما في المجموعة الثالثة فقد وجد اختلاف في تصنيف الزيت بين التحليل الحسي والتحليل الكيميائي (تقدير الأسترات) لـ 31 عينة زيت زيتون بكر. لقد توصلنا إلى مؤشر جديد لتوصيف زيت زيتون بكر ممتاز عندما تكون الكمية الكلية من الأسترات الألكيلية أقل من 75 ملغ\كغ أو إذا كانت بين 75 و 150 ملغ\كغ فيجب أن تكون العلاقة بين أسترات الايتيل والميتيل اصغر أو تساوي 1,5. تبين أن الأسترات الألكيلية هي معيار جيد لتحديد جودة زيت الزيتون البكر الممتاز. A new method was developed in this research to estimate the alkyl esters by isolating them using a cartridge of silica gel (SPE-1g). They were estimated by GC. The study samples were divided into 3 groups: extra virgin olive oils, oils with common sensory defects, and olive oils analyzed by team test. In the first group, esters were estimated in 49 samples. The results indicated that in 96% of samples, the total amount of alkyl esters were less than 75 mg/kg. For oils having a higher value, the relationship between esters (ethyl/methyl) was less than 1.5; but the oils upon which the above conditions do not apply lose quality status. In the second group, the esters were estimated in 5 olive oil samples with common sensory defects (fusty, winey, muddy sediment, musty, rancid and frosted olives). It was found that the changes resulted from enzymatic or fermentation processes accompanied by high concentrations of methyl (62-777) and ethyl esters (430 -1853), and the relationship between them ranged from 2.0 to 7.3. In the third group, differences were found in oil classification between sensory analysis and chemical analysis (esters estimate) for 31 sample virgin olive oil. We have reached a new indicator to characterize the extra virgin olive oil when the total amount of alkyl esters is less than 75 mg/ kg. If it ranged between 75 and 150 mg/kg, the relationship between ethyl and methyl esters should be smaller or equal to 1,5. The alkyl esters are a good indicator to determine extra virgin olive oil quality.